1998
DOI: 10.1023/a:1005995806897
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The seed storage proteins of Coix, sorghum and maize are codified by homologous genes which are coordinately expressed in the endosperm in a temporal-specific fashion. Opaque2 (O2), a bZIP protein originally isolated from maize, has been described as a transcription activator of alpha- and beta-prolamin genes. The isolation and characterization of cDNA and genomic clones encoding the Opaque2 homologue from Coix are reported here. The coding region of the Coix O2 gene is interrupted by five introns and codifies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…5B, high levels of GUS activity were detected in aleurone and subaleurone layers of maturing seeds and not in the embryo tissues. Highly sensitive fluorometric assays also showed that GUS activity was not (19) were from barley, O2 (15) and OHP1 (34) from maize, SPA (5) from wheat, O2-sorg from sorghum (38), and O2-coix from coixin (39). detected in roots, leaf, stem, and anthers (data not shown).…”
Section: Isolation Of Cdna Clones Encoding Bzip Transcription Factor mentioning
confidence: 95%
“…5B, high levels of GUS activity were detected in aleurone and subaleurone layers of maturing seeds and not in the embryo tissues. Highly sensitive fluorometric assays also showed that GUS activity was not (19) were from barley, O2 (15) and OHP1 (34) from maize, SPA (5) from wheat, O2-sorg from sorghum (38), and O2-coix from coixin (39). detected in roots, leaf, stem, and anthers (data not shown).…”
Section: Isolation Of Cdna Clones Encoding Bzip Transcription Factor mentioning
confidence: 95%
“…Garcia and Villarroel (2009) found that corn gluten had a positive influence on macrophage phagocytosis in tilapia (Oreochromis niloticus L.), and the number of bacteria that was phagocytosed by macrophages was significantly increased at 4-h postinfection. The nucleotide and amino acid sequence of Coix exhibited high homology with wheat and corn (Ary, Shewry, & Richardson, 1988;Vettore et al, 1998). Thus, the function of CGH on immune system is worth to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic, molecular and biochemical analyses indicate that bZIPs are regulators of important plant processes such as organ and tissue differentiation [26][30], cell elongation [31], [32], nitrogen/carbon balance control [33], [34], pathogen defence [35][40], energy metabolism [41], unfolded protein response [42], [43], hormone and sugar signalling [44][47], light response [48][50], osmotic control [34], [51], and seed storage protein gene regulation [52]. Initially, 50 plant bZIP proteins were classified into five families, taking into account similarities of their bZIP domain [53]. An original investigation of the complete Arabidopsis thaliana genome sequence indicated the presence of 81 putative bZIP genes [54], [55].…”
Section: Introductionmentioning
confidence: 99%